2022
DOI: 10.3390/rs14153703
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Human Health: Investigating the Moderating Effect of the Built Environment

Abstract: Air pollution seriously threatens human health and even causes mortality. It is necessary to explore effective prevention methods to mitigate the adverse effect of air pollution. Shaping a reasonable built environment has the potential to benefit human health. In this context, this study quantified the built environment, air pollution, and mortality at 1 km × 1 km grid cells. The moderating effect model was used to explore how built environment factors affect the impact of air pollution on cause-specific morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Then, the correlation analysis, as a preliminary analysis, was used to explore how the Ess impact heat waves and heat-related mortality This study used the correlation analysis to study the relationship between the two. Pearson's correlation coefficient can measure the correlation between two variables, x and y [53]. The coefficient r is calculated as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Then, the correlation analysis, as a preliminary analysis, was used to explore how the Ess impact heat waves and heat-related mortality This study used the correlation analysis to study the relationship between the two. Pearson's correlation coefficient can measure the correlation between two variables, x and y [53]. The coefficient r is calculated as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Buildings make a great contribution to the total energy consumption of cities, accounting for about 32%, which is the key to urban energy conservation and pollution emissions reduction (Lucon et al, 2014 ). The main methods of lowering energy consumption of buildings consist of using energy-saving reconstructions of building envelope and changing the built environment (Kim et al, 2019; Wang et al, 2022a ). Among these, the elements of built environment can sustainably affect the energy use by modifying the microclimate around buildings, such as land use and land cover (LULC) (Qiao & Liu, 2020 ; Soydan, 2020 ), landscape structure (Chen et al, 2011 ; Haas & Ban, 2014 ), building configuration (Deng & Wong, 2020 ; Leng et al, 2020 ; Wong et al, 2011 ) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the outbreak of the COVID-19 pandemic has brought global health challenges in recent years, especially mental disorders (Farzadfar et al, 2022 ; Ge et al, 2022 ; Liu et al, 2022 ). Sustainable environment may have a positive social impact, such as by benefiting human health, improving residents’ thermal comfort and quality of life (Aman et al, 2019 ; Li et al, 2022 ; Wang et al, 2022a , 2022b ; Yuan et al, 2021 ). Therefore, how to low building energy consumption, improve the urban thermal environment and achieve the goal of sustainable development by optimizing the environment of cities has received attention from policymakers and scholars increasingly (Aman et al, 2022 ; Wang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that built environments can mitigate the adverse health effects of air pollution. It has proved that built environment in Nanjing moderated the relationship between air pollution and non-accident mortality ( 6 ). Specifically, SHDI and water area can mitigate the effect of PM 2.5 on all-cause mortality ( 6 ).…”
Section: Introductionmentioning
confidence: 99%